Polyphenols Sensitization Potentiates Susceptibility of MCF-7 and MDA MB-231 Cells to Centchroman - Singh, Neetu; Zaidi, Deeba; Shyam, Hari; Sharma, Ramesh; Balapure, Anil Kumar (PLOS ONE, 2012)
Polyphenols as “sensitizers” together with cytotoxic drugs as “inducers” cooperate to trigger apoptosis in various cancer cells. Hence, their combination having similar mode of mechanism may be a novel approach to enhance the efficacy of inducers. Additionally, this will also enable to achieve the physiological concentrations facilitating significant increase in the activity at concentrations which the compound can individually provide. Here we propose that polyphenols (Resveratrol (RES) and Curcumin (CUR)) pre-treatment may sensitize MCF-7/MDA MB-231 (Human Breast Cancer Cells, HBCCs) to Centchroman (CC, antineoplastic agent). 6 h pre-treated cells with 10 µM RES/CUR and 100 µM RES/30 µM CUR doses, followed by 10 µM CC for 18 h were investigated for Ser-167 ER-phosphorylation, cell cycle arrest, redox homeostasis, stress activated protein kinase (SAPKs: JNK and p38 MAPK) pathways and downstream apoptosis effectors. Low dose RES/CUR enhances the CC action through ROS mediated JNK/p38 as well as mitochondrial pathway in MCF-7 cells. However, RES/CUR sensitization enhanced apoptosis in p53 mutant MDA MB-231 cells without/with involvement of ROS mediated JNK/p38 adjunct to Caspase-9. Contrarily, through high dose sensitization in CC treated cells, the parameters remained unaltered as in polyphenols alone. We conclude that differential sensitization of HBCCs with low dose polyphenol augments apoptotic efficacy of CC. This may offer a novel approach to achieve enhanced action of CC with concomitant reduction of side effects enabling improved management of hormone-dependent breast cancer.